Descripción de 3 observatorios de radiación cósmica - Anderson, J. C.; Cardoso, J. N.; Cicchini, A. A.; Ghielmetti, H. S.; Manzano, J. R.; Santochi, C. R. (Comisión Nacional de Energía Atómica; Argentina, 1958)
Fil: Anderson, J. C. Comisión Nacional de Energía Atómica; Argentina